Dichotic Listening Deficit Associated With Solvent Exposure. Issue 6 (July 2017) - Landry, Simon P.; Fuente, Adrian
Abstract : Hypothesis: A significant left ear deficit can be observed in solvent-exposed individuals using the dichotic digit test. Background: Solvents are ubiquitous in global industrial processes. Due to their lipophilic nature, solvents can adversely affect large white matter tracks such as the corpus callosum. Previous investigations reveal that long-term workplace exposure to solvents is also deleterious to various auditory processes. Investigations in exposed populations suggest a decreased performance for dichotic listening. Methods: In this present study, we examined the lateralization of a dichotic digit test score for 49 solvent-exposed individuals along with 49 age- and sex-matched controls. We evaluated group differences between test scores and the right ear advantage using a laterality index (LI). Results: Individual ear results suggest that long-term workplace solvent exposure is associated with a significantly lower dichotic listening score for the left ear. A binaural compound score analysis using a laterality index supports this left-ear deficit. Conclusion: These results provide an insight on the effects of solvent exposure on dichotic listening abilities. Further research should investigate the importance of using dichotic listening tasks to screen for solvent-induced auditory dysfunction in exposed individuals.